Cytopathology of a Rare Case of Osteosarcoma in a Murrah Buffalo (Bubalus Bubalis) - Leishangthem, Geeta D.; Jaiswal, Vikas; Gupta, Kuldip; Singh, Nittin D.; S. Randhawa, Swaran (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Osteosarcomas are the malignant tumors of bones that may arise directly from bone or metastasis from other  organs. There is involvement of various cells like osteoblast,  chondroblast, fibroblast, etc. Osteosarcomas are commonly  reported in dogs and cats but rarely in large animals. Benign  tumors are much more common in large animals than  sarcomas (Thompson and Pool, 2002). There are very few  reports on osteosarcoma in cattle (Naghshineh et al., 1991;  Plumlee et al., 1993; Prins et al., 2012; Micheloud et al., 2015;  Santos et al., 2016). However, rarely observed in buffaloes  (Silveira et al., 2010). The present communication reports a  rare case of metastatic osteoblastic osteosarcoma involving  the trachea of a Murrah buffalo through a cytological  approach using Fine Needle Aspirates (FNA).
Keywords: Cytopathology; Osteosarcoma; Murrah Buffalo